The Relationship Between Health Promotion Intensity And Public Health Behavior - Lumastari Ajeng Wijayanti; Musdalifah Musdalifah; Asriani Hijrah; Edi Pramono (International Journal of Health Sciences, 2026)
Health promotion is a strategic effort to increase public health awareness, knowledge, and behavior. Continuous health promotion is expected to encourage behavioral changes towards a healthy lifestyle. This study aims to determine the relationship between the intensity of health promotion and public health behavior. The study used an observational analytical design with a cross-sectional approach. The study sample consisted of 120 adult respondents selected using a purposive sampling technique. Data were collected through a health promotion intensity questionnaire and a health behavior questionnaire. Data analysis was performed using the Chi- Square test. The results showed a significant relationship between the intensity of health promotion and public health behavior (p < 0.05). It was concluded that the higher the intensity of health promotion, the better the public health behavior.